1987
DOI: 10.1590/s0373-55241987000100008
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia, distribuição e abundância de Trachurus lathami Nichols, 1920 (Teleostei: Carangidae) na região sudeste-sul do Brasil

Abstract: M orphologiaal drlta of horse-maakerel (TMeh~ latham~)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
10

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 9 publications
(6 reference statements)
1
8
0
10
Order By: Relevance
“…Comparison of the growth parameters obtained here with previous estimates in Brazil (Table 3) showed that the growth pattern and age structure of T. lathami have been stable (Saccardo andKatsuragawa 1995, Saccardo et al 2005). However, the rough scad has historically presented seasonal displacements within the SEBB, resulting in variations in the space-time distribution of the individuals in each age (Saccardo 1987, Saccardo andHaimovici 2007).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Comparison of the growth parameters obtained here with previous estimates in Brazil (Table 3) showed that the growth pattern and age structure of T. lathami have been stable (Saccardo andKatsuragawa 1995, Saccardo et al 2005). However, the rough scad has historically presented seasonal displacements within the SEBB, resulting in variations in the space-time distribution of the individuals in each age (Saccardo 1987, Saccardo andHaimovici 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Previous information on the presence of up to 400 mm TL rough scads at the SEBB (Menezes and Figueiredo 1980) denotes very rare individuals, never recorded again. Historically, the longer total lengths recorded for the rough scad in the SEBB were 260 mm (Saccardo 1987), 207 mm (Figueiredo et al 2002), 240 mm (Saccardo et al 2005) and 261 mm (Bernardes et al 2005). In all these studies, as well as in our results, individuals larger than 200 mm were seldom recorded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations